Molecular studies of rust on European aspen suggest an autochthonous relationship shaped by genotype - Siddique, Abu Bakar; Menke, Laura; Dinedurga, Melis; Albrectsen, Benedicte Riber (Frontiers in Plant Science, 2023)
Forests are at increasing risk from pathogen outbreaks because human activities may naturalize exotic pathogens and climate change may make native diseases more severe. Robust pest surveillance routines are therefore needed to support forest management. Pine infestation by Melampsora pinitorqua (pine twisting rust) can reduce pine wood quality and is therefore of concern in Swedish forestry. Visible rust scores (VRS) are used to measure the local infestation density of M. pinitorqua on its obligate alternate host aspen (Populus tremula), and here we evaluate the use of VRS as a tool for quantification of Melampsora in aspen leaves. We use molecular methods to compare VRS for aspen leaves from a common garden in northern Sweden to the abundance of rust DNA in the same leaves. Analysis of genetic markers associated with Melampsora revealed differences between aspen genotypes that correlated with the abundance of both a general fungal genetic marker (amplifying the ITS2 region of the fungal rDNA sequence) and DNA sequences specific to Melampsora. Additional PCR experiments using species-specific primers confirmed the presence of M. pinitorqua in the leaves and the abundance of the markers could be used for quantification. However, no sequences specific for two exotic rusts (M. medusae and M larici-populina) were detected. We hypothesized that condensed tannin (CT) defense compounds in the leaves might affect the reliability of VRS. At the population level, foliar CT concentrations correlated negatively with the abundance of general fungal genetic markers and rust-specific markers. However, at the genotype level both positive and negative relationships were observed between CTs, fungal markers, and rust infestations.